2010
DOI: 10.1051/0004-6361/200913020
|View full text |Cite
|
Sign up to set email alerts
|

zCOSMOS – 10k-bright spectroscopic sample

Abstract: We present the galaxy stellar mass function (GSMF) to redshift z 1, based on the analysis of about 8500 galaxies with I < 22.5 (AB mag) over 1.4 deg 2 , which are part of the zCOSMOS-bright 10k spectroscopic sample. We investigate the total GSMF, as well as the contributions of early-and late-type galaxies (ETGs and LTGs, respectively), defined by different criteria (broad-band spectral energy distribution, morphology, spectral properties, or star formation activities). We unveil a galaxy bimodality in the glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
309
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 416 publications
(355 citation statements)
references
References 145 publications
(238 reference statements)
41
309
2
Order By: Relevance
“…with similar redshift of formation [15]), which means that they represent an homogeneous sample in terms of ages of formation, and can be used as "cosmic chornometers". Moreover, basing on the stellar mass function [16] and clustering [63], it has been found that this population of galaxies experienced negligible major merging events in a large fraction of the redshift range considered in our study [64], i.e. they did not increase their mass significantly in the time comprised between the redshifts adopted for the differential approach, meaning that the contamination to the initial population (with a given age of formation) is minimal.…”
Section: Goods-s Samplementioning
confidence: 54%
See 4 more Smart Citations
“…with similar redshift of formation [15]), which means that they represent an homogeneous sample in terms of ages of formation, and can be used as "cosmic chornometers". Moreover, basing on the stellar mass function [16] and clustering [63], it has been found that this population of galaxies experienced negligible major merging events in a large fraction of the redshift range considered in our study [64], i.e. they did not increase their mass significantly in the time comprised between the redshifts adopted for the differential approach, meaning that the contamination to the initial population (with a given age of formation) is minimal.…”
Section: Goods-s Samplementioning
confidence: 54%
“…Based on a plethora of observational results, there is general agreement that these are typically massive (M stars ∼ 10 11 M ⊙ ) early-type galaxies (ETGs hereafter) which formed the vast majority (>90%) of their stellar mass at high-redshifts (z > 2 − 3) very rapidly (∼0.1-0.3 Gyr) and have experienced only minor subsequent episode of star formation, therefore being the oldest objects at all redshifts (e.g. [13][14][15][16]). Thus, a differential dating of their stellar populations provides dt in Eq.…”
Section: Contents 1 Introductionmentioning
confidence: 94%
See 3 more Smart Citations